The Resurrection of Jesus as a Historical Claim: A Theological-Legal Analysis of the Evidence and a Critical Examination of the Christian Faith - John Abraham Christiaan (Sekolah Tinggi Teologi Transformasi Indonesia, 2026)
The resurrection of Jesus remains one of the most debated events in Christian theology, with various objections questioning its historical credibility and evidential basis. This study examines the historical evidence for Jesus' resurrection through an interdisciplinary theological-juridical approach by employing the principles of the law of evidence as an analytical framework. Using a qualitative research design based on historical, theological, and documentary analysis, the study evaluates biblical eyewitness testimony, the witness of the Apostolic Fathers, and relevant non-Christian historical sources within the categories of direct, circumstantial, testimonial, and documentary evidence. The findings demonstrate that these sources collectively satisfy the principles of evidential consistency, corroboration, and plurality required in the law of evidence. Conversely, the major objections to the resurrection fail to provide sufficient evidential support to invalidate the historical testimony. This study argues that the resurrection of Jesus can be understood not only as the foundation of Christian faith but also as a historically grounded event supported by coherent and cumulative evidence. The study contributes a novel interdisciplinary framework by integrating theological inquiry, historical investigation, and legal evidentiary analysis into contemporary Christian apologetics.